Analisis Integritas Petugas Pemutakhiran Data Pemilih dalam Pendataan Pemilih pada Pemilihan Walikota dan Wakil Walikota Medan Tahun 2020 di Kecamatan Medan Polonia - Dwi Gustia Ningsih; R. Hamdani Harahap; Heri Kusmanto (Universitas Medan Area, 2023)
The purpose of this study was to determine the integrity of the PPDP in terms of aspects of honest behavior, commitment to vision and mission, acting wisely, being disciplined and responsible, and behaving nobly in acting towards voter data collection in the 2020 Medan mayoral and deputy mayoral elections in Medan Polonia subdistrict. In addition, it is also to find out the standard operating procedure that lies behind the integrity of the PPDP in collecting voter data for the 2020 Medan Mayor and Deputy Mayor elections in the Medan Polonia sub-district. The DPT problem started with the data collection process carried out by PPDP by visiting voters directly to match voter data. The research method used is qualitative-descriptive, while the data analysis technique consists of data reduction, data presentation and drawing conclusions. The research results obtained were (1) the integrity of the Medan Polonia District PPDP as a whole could be questioned because there were PPDP elements who did not submit proof of voter registration to residents who had been recorded. PPDP elements also do not cross out voters who no longer meet the requirements and are not registered on the DPT.